Pengaruh Biaya Promosi dan Tingkat Margin Terhadap Peningkatan Penyaluran Dana Pembiayaan Murabahah - Danil Syahputra (Jurnal Penelitian Medan Agama, 2019)
This research discusses the influence of promotion cost and margin level to increase the distribution of Murabahah Financing Fund at PT. BPRS Amanah Bangsa. The objective is to observe and to know empirically the effect of promotional costs and margin rates on increasing the distribution of murabahah financing funds at PT. BPRS Amanah Bangsa. Sampling is done by retrieving the promotional cost data and margin level as well as the volume of fund disbursement from 2013 to 2015 (36 months). Multiple linear regression is used as an analytical technique. The results showed that the cost of promotion and margin level both significantly affect the increase in the fund distribution of murabahah financing. From the results of regression analysis It is known that the promotion cost variable has a stronger influence than the margin level variable against the distribution of Murabahah financing funds.